A case of Hodgkin's disease and non-Hodgkin Lymphomas, occurred in different anatomical sites at simultaneous onset - Maeda, Kunihiko; Hashimoto, Hideki; Imai, Yutaka; Matsuda, Mikio; Ikeda, Hideyuki; Takahashi, Katsuro; Shindo, Tetsuro; Narabayashi, Masaru; Masunaga, Atsuko (Journal of the Japan Society of the Reticuloendothelial System, 1989)
Discordant malignant lyphoma composed of Hodgkin's disease (HD) and non-Hodgkin lymphoma (NHD) which occurred in a 38 years-old Japanese male is reported. He suffered from slight fever (38°C), general fatigue since December 25 in 1985. Thereafter, axiller and inguinal lymph nodes swelling was noticed. Because of systemic lymph node swelling with anemia, he was hospitalized in Nagai City Hospital 2 weeks later. Cervical, axillar and inguinal lymph nodes were excised. He was received chemotherapy (Adr, End. Prd. L-Asp). 6 months after, he was transfered to Yamagata Prefectural Central Hospital. In spite of chemotherapy, he died of a clinically suspicious perforation of alimentary tract in January 1986. Autopsy was not permitted. Resected cervical and inguinal nodes revealed scattered mononucleated Hodgkin's (H) cells and multinucleated Reed-Sternberg (RS) cells with intermingled lymphocytes, eosinophils and plasma cells, so they were diagnosed as HD, mixed cellularity (MC) type. Axillar node showed a diffuse proliferation of small and large mononucleated cells with prominent nucleoli, without diagnostic H cells and/or RS cells, and diagnosed as NHL, diffuse, mixed. Immunohistochemically, some of H cells and RS cells in cervical and inguinal nodes were positive for B1, MB1 and polyclonal cIgs (IgG, A, κ/IgG, A κ, λ). On the other hand, tumor cells in axillar node showed monoclonal cIg (IgG, κ). In the nodes of HD, there were small number of medium sized cells, which had a nucleus with prominent nucleolus and dispersed chromatin and were positive for B cell markers (B1, MB1) and polyclonal cIgs (IgG, A, κ/IgG, κ λ). LeuM1 was not detected in H cells, RS cells and diffuse lymphoma cells. This case was suggestive that some sort of HD was of lymphocyte origin and has some possibilities to develop a simultaneous progression to diffuse lymphoma.